2000
DOI: 10.1016/s0022-5347(05)67411-3
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Position in the Androgen Insensitivity Syndrome: Implications for the Role of Androgens in Testicular Descent

Abstract: Testicular position correlates with genital phenotype in patients with androgen receptor mutations, supporting a major role for androgens in testicular descent. Inguinal hernia and abnormal pelvic ligaments in these individuals may partially determine testicular position but to our knowledge the role of androgen receptors, if any, in their development is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(20 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Because both mutations are found in androgen insensitivity (reviewed in Ref. 40), these results argue that this medical condition may arise from a defect in the N-to-C interaction of AR. In view of this, the c-Jun-positive effect on hAR N-to-C interaction is likely to be physiologically relevant and responsible for the c-Jun enhancement of hAR transactivation.…”
Section: Discussionmentioning
confidence: 93%
“…Because both mutations are found in androgen insensitivity (reviewed in Ref. 40), these results argue that this medical condition may arise from a defect in the N-to-C interaction of AR. In view of this, the c-Jun-positive effect on hAR N-to-C interaction is likely to be physiologically relevant and responsible for the c-Jun enhancement of hAR transactivation.…”
Section: Discussionmentioning
confidence: 93%
“…This is well exemplified by the role of the androgen receptor (AR) 1 in male sexual development, which is disrupted in males with androgen insensitivity syndrome (for review, see Ref. 1).…”
mentioning
confidence: 99%
“…One study showed that out of 52 patients with the CAIS diagnosed, 35 (67%) had abdominal, 16 had inguinal, and one had labial testes. [8] The main differential diagnosis for CAIS are complete gonadal dysgenesis (Swyer syndrome) which is distinguished by poor breast development, short stature, and true hermaphrodism which can be differentiated by some degree of masculinization, presence of ovarian tissue on histology specimen.…”
Section: Discussionmentioning
confidence: 99%